Pengaruh Kemampuan Phonological Awareness terhadap Kemampuan Literasi pada Anak Kelas Satu di Kota Surakarta - Fitri, Anisyah Dewi Syah; Setyaningsih, Wiwik (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Phonological awareness is crucial in the early school process, as it is foundational for reading and writing skills. However, research data on the phonological awareness of elementary school-age children in Indonesia remains scarce. Objectives: This study aimed to determine the effect of a phonological awareness intervention on the literacy skills of first-grade elementary school children in Surakarta. Methods: This study employed a quasi-experimental design using a one-group pretest-posttest approach23. A sample of 30 children was selected using total sampling. The intervention was administered over 2 weeks, consisting of 6 sessions, each lasting 45 minutes. The instruments used were early literacy and phonological sensitivity tests, analyzed using the Wilcoxon test. Results: Pre-intervention literacy skills showed 28 children (93.3%) in the